O problema do mal no livre arbítrio de Santo Agostinho - Mattos, José Roberto Abreu de (2013)
The aim of this monographic paper is to reflect upon the problem of evil. For a better understanding of the subject we decided to approach fundamental issues issues such as : what is evil, the reason of evil, its origen and mainly the meaning of evil and its suffering in relation to one s free will. Appealing to specialized bibliography, other concepts are seen essential for the understanding of this subject like: grace, freedom, divine prescience, will, love and so on. Basically all the answers about the issue of evil envolve directly or indirectly a reflection about God, in other words everything about evil envolves human suffering, and one of the strong points regarding modern atheism is why do I suffer? Where is God? Well, looking precisely through this prespective that is, approaching the issue of evil together with the issue of God arises the legitimaly and necessity to conceive and defend a right concept of as being almighty googd and fair